A Comparative Analysis of the Outcomes of Carotid Stenting and Carotid Endarterectomy in the Management of Carotid Stenosis - Saad, Hasan I. Fadel; Noom , Mustafa; Shnab, Khalid; Osta, Abdel Magid El (Al-Mukhtar Journal of Sciences, 2019)
Carotid Stenosis is an important cause of stroke (20%) which is associated with high morbidity and mortality rates. The management is mainly by surgery or carotid stenting. This study reviews 3 years of experience and the outcomes in the treatment of carotid stenosis by the two methods. The study aimed to evaluate and compare the outcomes of both procedures during a 3yr period at a vascular Surgery department of the Cisanello Hospital. 302 pts were retrospectively analyzed; 151 pts assigned for each procedure. The average intervention time was significantly higher for the CEA group O.R: 0.556; 95% C.I; 0.349- 0.886, P: 0.014 but technical successes were achieved in 100% of CEA pts, whereas were achieved in 91.39% of the CAS group. The periprocedural stroke was nonsignificant between the two procedures. The Periprocedural TIA were show significant difference with more incidences in CAS pts [O.R: 7.292, 95% C.I; 1.150- 45.856, P: 0.032] but almost all pts improved. The cranial nerve injuries were a specific complication of CEA [11.9%]. The recurrent stenosis was seen only in CAS pts [2.9%] with O.R: 0.493, 95% C.I; 0.104- 2.345, P: 0.410. Both procedures are effective and comparable in outcomes in the management of carotid Stenosis.